2020
DOI: 10.3390/ma13215039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Inhomogeneous Material on the Fracture Mechanisms of Bamboo by Finite Element Method

Abstract: Bamboo is a remarkably strong and sustainable material available for construction. It exhibits optimized mechanical characteristics based on a hollow-inhomogeneous structure which also affects its fracture behavior. In this study, the aim is to investigate the effect of material composition and geometrical attributes on the fracture mechanisms of bamboo in various modes of loading by the finite element method. In the first part of the investigation, the optimized transverse isotropy of bamboo to resist transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Leveraging the recent growth of 3D reconstruction methods to recover accurate tree structures from 3D point clouds, we aimed to unveil the relationship between the morphological and mechanical properties of trees. First, we hypothesized that the branch-growing process is mechanically unstable in terms of compressive and tensile stresses, and verified it by performing mechanical simulations using the finite element method, which is a similar approach to the recent works 24 , 25 . Using the mechanical results, we constructed a theoretical formulation of tree branch depending on mechanics, shape, and growth based on the axiom of constant stress 6 , 26 .…”
Section: Introductionmentioning
confidence: 84%
“…Leveraging the recent growth of 3D reconstruction methods to recover accurate tree structures from 3D point clouds, we aimed to unveil the relationship between the morphological and mechanical properties of trees. First, we hypothesized that the branch-growing process is mechanically unstable in terms of compressive and tensile stresses, and verified it by performing mechanical simulations using the finite element method, which is a similar approach to the recent works 24 , 25 . Using the mechanical results, we constructed a theoretical formulation of tree branch depending on mechanics, shape, and growth based on the axiom of constant stress 6 , 26 .…”
Section: Introductionmentioning
confidence: 84%
“…Under bending, buckling can also occur in thin-walled tube. It was observed that bamboo has excellent ability to resist buckling when subjected to bending and shear [23] and local buckling is not considered as a critical mechanism [50]. As local buckling depends on adjusting the slenderness ratio and diameterthickness ratio [51], the tapering structure of bamboo would be the cause of this ability.…”
Section: Discussionmentioning
confidence: 99%
“…(1) From the ovalization of the cross section, which causes the culm to kink locally, or the Brazier effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…For the simulation-based methods, de Oliveira et al 28 conducted a statistical design to evaluate the effect of the integrated bamboo diameter and the adhesive tape on the maximum load, for which a non-linear Finite Element (FE) analysis is developed to simulate the low-velocity impact test and to predict the failure mechanisms of the skins, bamboo integrated core, and adhesive. Ramful et al 29 used the finite element method to investigate the effect of inhomogeneous material on the fracture mechanisms of bamboo-based materials, and a numerical study of fracture mechanisms in bending, compression, torsion, and shear loadings is finalized. This study's results guide the optimal and safe design of bamboo-integrated products and constructions.…”
Section: Introductionmentioning
confidence: 99%